(untitled) (Journal of the College of Basic Education, 2024)
The experiment was carried out during the 2022-2023 season, in the Department of Science / College of Basic Education / Al-Mustansiriya University, to determine the effect of Foliartal fertilizer and Acadian organic fertilizer on the the Adhatoda vasica L plant. The experiment was designed with completely randomized blocks (RCBD) and three replicates that included three concentrations of foliar fertilizer (0, 4, 8) ml/L and three concentrations of organic fertilizer (0, 1, 2) g/L. The results of treating the plants with foliar fertilizer showed a significant increase in the traits. The results showed that a concentration of 8 ml/liter of foliar fertilizer achieved the highest significant increase in plant height, number of leaves, leaf area, and total chlorophyll. The high concentration of foliar fertilizer also caused a significant increase in the plant’s substance Vasicine. Also, treating plants with organic fertilizer had a positive effect on the studied traits. Double the recommended concentration of organic fertilizer achieved a significant increase in plant height, number of leaves, leaf area, total chlorophyll, and plant substance Vasicine. The interaction between the treatments showed a significant increase in most of the studied traits in particular When combined with 8 ml/L of foliar fertilizer and twice the amount of organic fertilizer.